2007
DOI: 10.1210/en.2007-0446
|View full text |Cite
|
Sign up to set email alerts
|

A Splicing Variant of the Androgen Receptor Detected in a Metastatic Prostate Cancer Exhibits Exclusively Cytoplasmic Actions

Abstract: The androgen receptor (AR) is a ligand-activated transcription factor that displays genomic actions characterized by binding to androgen-response elements in the promoter of target genes as well as nongenomic actions that do not require nuclear translocation and DNA binding. In this study, we report exclusive cytoplasmic actions of a splicing variant of the AR detected in a metastatic prostate cancer. This AR variant, named AR23, results from an aberrant splicing of intron 2, wherein the last 69 nucleotides of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 45 publications
1
63
0
Order By: Relevance
“…When these four cell lines were compared using miRNA microarray analyses, mir-184, mir-361, and mir-424 were significantly up-regulated, and mir-19b, mir-29b, mir128b, mir-146a, mir-146b, mir-221, mir-222, and mir-663 were down-regulated in HRPC-related LNCaP C4-2B and PC3 cells as compared to androgen-dependent LNCaP and PC3-AR9 cells. Only mir-184 has been proposed to possess oncogenic activities in prostate cancer (Jagla et al 2007). A recent study demonstrated that an aberrant splicing variant of androgen receptor, AR23, contained 69 nt of the intron 2 sequence, which separated the two AR zinc fingers required for nuclear entry (Jagla et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…When these four cell lines were compared using miRNA microarray analyses, mir-184, mir-361, and mir-424 were significantly up-regulated, and mir-19b, mir-29b, mir128b, mir-146a, mir-146b, mir-221, mir-222, and mir-663 were down-regulated in HRPC-related LNCaP C4-2B and PC3 cells as compared to androgen-dependent LNCaP and PC3-AR9 cells. Only mir-184 has been proposed to possess oncogenic activities in prostate cancer (Jagla et al 2007). A recent study demonstrated that an aberrant splicing variant of androgen receptor, AR23, contained 69 nt of the intron 2 sequence, which separated the two AR zinc fingers required for nuclear entry (Jagla et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…This variant results from aberrant splicing of intron 2, resulting in the insertion of 23-amino acids between the two zinc-fingers of the DNA-binding domain. This AR-variant is exclusively localized in the cytoplasm (34). AR recognizes and binds to respective responsive elements (ARE) representing two hexameric direct repeats (AGAACA) separated by a three nucleotide spacer, with the half site repeated on the same strand.…”
Section: Steroid and Thyroid Hormone Receptor Structurementioning
confidence: 99%
“…Importantly, cytoplasmic DHTactivated AR23 remains partially active, with the ability to activate transcription from androgen-responsive promoters. Such novel cytoplasmic actions for this splicing AR variant suggest possible contribution in PrC progression [29].…”
Section: Androgen Receptor Co-activators and Co-repressorsmentioning
confidence: 92%
“…One AR variant, AR23, results from AS of intron 2, in which the last 69 nucleotides of the intronic sequence are retained, leading to the insertion of 23 amino acids between the two zinc fingers in the DNA-binding domain [29]. Upon ligand binding (dihydrotestosterone [DHT]), nuclear entry of AR23 is impaired.…”
Section: Androgen Receptor Co-activators and Co-repressorsmentioning
confidence: 99%